An automated microreactor for semi-continuous biosensor measurements. Issue 8 (22nd March 2016) - Buffi, Nina; Beggah, Siham; Truffer, Frederic; Geiser, Martial; van Lintel, Harald; Renaud, Philippe; van der Meer, Jan Roelof
Abstract : An automated microreactor for culturing bactosensor cells for subsequent sample exposure gives excellent possibilities for on-line consecutive measurements. Abstract : Living bacteria or yeast cells are frequently used as bioreporters for the detection of specific chemical analytes or conditions of sample toxicity. In particular, bacteria or yeast equipped with synthetic gene circuitry that allows the production of a reliable non-cognate signal ( e.g., fluorescent protein or bioluminescence) in response to a defined target make robust and flexible analytical platforms. We report here how bacterial cells expressing a fluorescence reporter ("bactosensors"), which are mostly used for batch sample analysis, can be deployed for automated semi-continuous target analysis in a single concise biochip. Escherichia coli -based bactosensor cells were continuously grown in a 13 or 50 nanoliter-volume reactor on a two-layered polydimethylsiloxane-on-glass microfluidic chip. Physiologically active cells were directed from the nl-reactor to a dedicated sample exposure area, where they were concentrated and reacted in 40 minutes with the target chemical by localized emission of the fluorescent reporter signal. We demonstrate the functioning of the bactosensor-chip by the automated detection of 50 μgarsenite-As l −1 in water on consecutive days and after a one-week constant operation. Best induction of the bactosensors of 6–9-fold to 50 μg l −1 was found at an apparent dilution rate of 0.12 h −1 in the 50 nl microreactor. The bactosensor chip principle could be widely applicable to construct automated monitoring devices for a variety of targets in different environments.